2014
DOI: 10.4238/2014.july.24.18
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor genetic variants are associated with susceptibility of gallbladder adenocarcinoma in a Chinese cohort

Abstract: ABSTRACT. The aim of this study was to test for the possible association between vitamin D receptor (VDR) genetic variants and susceptibility to gallbladder cancer (GBC). A total of 291 GBC cases were recruited and 396 gender-and age-matched healthy volunteers were enrolled as controls. The VDR gene polymorphisms were determined in all subjects. The genotype and the allele frequencies of ApaI, BsmI, and TaqI polymorphisms were not significantly different between GBC subjects and controls. However, the genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Hence there is a great need to explore genes related to GBC susceptibility. Table 8[30,214-273] shows an overview of candidate gene studies reported in GBC.…”
Section: Methylation and Gallbladder Cancermentioning
confidence: 99%
“…Hence there is a great need to explore genes related to GBC susceptibility. Table 8[30,214-273] shows an overview of candidate gene studies reported in GBC.…”
Section: Methylation and Gallbladder Cancermentioning
confidence: 99%
“…We choose 14 papers out of 96 which showed a statistically significant odds ratio for carriage of allele F in sexdependent cancers in male and female groups together [20][21][22][23][24][25][26][27][28][29][30][31][32][33] (p < 0.05). The results were inconsistent: allele F was reported to be associated with cancer risk in eight papers (BC, CRC, CM, LC, GBC) and allele f in six papers (BC, RCC, MM, HCC, BCC, PCa, CM) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%